Dampened autonomic nervous system responses to stress and substance use in adolescence. (6th July 2022) - Rahal, Danny; Alkon, Abbey; Shirtcliff, Elizabeth; Gonzales, Nancy; Fuligni, Andrew; Eskenazi, Brenda; Deardorff, Julianna
Abstract: We investigated whether parasympathetic and sympathetic nervous system (SNS) responses to social‐evaluative threat at age 14 were related to the number of substances used between ages 14 and 16 among Mexican‐origin adolescents ( N = 243; 70.4% had never used substances by 14). Participants completed the Trier Social Stress Test, while cardiac measures of parasympathetic and SNS activity were measured continuously using respiratory sinus arrhythmia (RSA) and pre‐ejection period (PEP), respectively. Participants reported whether they had ever used alcohol, marijuana, and cigarettes, and had ever vaped nicotine in their lifetime at ages 14 and 16. Multilevel models were used to test associations between RSA and PEP responses at age 14 and substance use at 16. Among youth who had not used substances by 14, dampened RSA and PEP responses, and profiles of greater coinhibition and lower reciprocal SNS activation between RSA and PEP, at age 14 were associated with using substances by 16. Among youth who used by 14, exaggerated PEP responses were associated with using more substances by age 16. Taken together, dampened autonomic responses to social‐evaluative threat predicted initiation of substance use over two years, and difficulties with coordination of physiological responses may confer risk for substance use in adolescence.